Devising a method for reducing active power corona losses based on changing the structural parameters of a power transmission line - Shevchenko, Sergii; Olubakinde, Eniola; Danylchenko, Dmytro; Nazarenko, Ihor; Savchenko, Natalia; Shylkova, Larysa (Eastern-European Journal of Enterprise Technologies, 2022)
This paper reports a study into the influence of the main design parameters of power transmission lines on energy losses associated with the corona discharge; a method has been devised to reduce them. The structure of the split-phase wire, the distance to the ground, and between the centers of the phases of the line are determined at the design stage. Based on these structural parameters, the value of specific energy losses associated with the corona discharge is calculated. Studying the impact exerted on the amount of losses by each structural parameter makes it possible at the design stage to determine the structure of a power transmission line (PTL) with low energy losses. Reducing energy loss when transporting it along the line is one of the most important issues in the strategy for the development of the energy industry at the stage of the "green transition". It has been established that most structural parameters have a weak effect on the values of corona losses, and, if there is a significant impact, the implementation of such solutions leads to a large increase in the cost of constructing an overhead transmission line. Based on the analysis of the results of calculations of corona losses in power transmission lines, it was determined that the corona losses in the middle phase of the transmission line are much greater than in the extreme phases. That has made it possible to devise a method for reducing power corona losses associated with the alignment of the capacities of all phases of PTL. This effect is achieved by calculating, based on the developed method, the splitting step of the middle phase of PTL. The calculation of the splitting step is based on the preliminary determination of the capacity of the extreme phases and the substitution of calculated values in the resulting expression for the splitting step. The possibility of such a reduction in corona losses should significantly increase the energy efficiency of AC power transmission lines, especially in areas with large periods of different weather that provoke the occurrence of a corona discharge on the wires of their phases. This circumstance causes an increase in this type of power loss.